Makna Hidup Pada Narapidana Vonis Seumur Hidup Di Lapas Kelas IIA Banda Aceh - Dwi Chandra Pranata Pranata; Suryanto Suryanto (Journal Psikologi Forensik Indonesia, 2022)
The meaning of life is things that are considered very important and valuable and provide special value for someone so that they deserve to be used as a purpose in life (the purpose in life).  This study aims to describe how the meaning of life and efforts to achieve the meaning of life in prisoners who are serving sentences with life sentences in Banda Aceh Class IIA Prison. This research uses a qualitative approach using phenomenological methods. Data collection was conducted by in-depth interviews of prisoners with life sentences. Data analysis is carried out by the process of coding, categorization and understanding the meaning of the phenomenon.  The results showed that the purpose of life that means a lot to prisoners is religion and family. To achieve this goal in life, prisoners carry out various positive activities in Prison. Activities initiated by the prison as well as routine independent activities carried out by prisoners in their daily lives serving life sentences